Ethnomathematics Based Geometry Module Development With a Scientific Approach to Improve Students' Metacognition Ability - Achmad Mutaqin; Mohammad Syaifuddin; Yus Mochamad Cholily (IndoMath: Indonesia Mathematics Education, 2021)
This study aims to develop a geometry module based on ethnomathematics with a scientific approach, test the module's validity and feasibility, and determine the effect of using modules in learning on students' metacognitive abilities. This study uses a research and development (R&D) approach with a 4D model (define, design, develop, and disseminate). The research subjects were students of 8rd Junior High School in Malang. Data analysis of the effect of the use of modules on metacognition abilities using the paired sample t-test. The research results showed the ethnomathematics based geomery module with a scientific approach is valid, developed by with a 4D model. The module is also categorized as effective for use in learning activities. The ethnomathematics based geometry modules with a scientific approach has an effect on metacognition abilities.